2021
DOI: 10.1038/s41562-021-01124-6
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic preference for art can be predicted from a mixture of low- and high-level visual features

Abstract: It is an open question whether preferences for visual art can be lawfully predicted from the basic constituent elements of a visual image. Here, we developed and tested a computational framework to investigate how aesthetic values are formed. We show that it is possible to explain human preferences for a visual art piece based on a mixture of low-and high-level features of the image. Subjective value ratings could be predicted not only within but also across individuals, with a regression model with the same s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 46 publications
6
79
0
Order By: Relevance
“…Neuroaesthetics research has focussed on deconstructing features of visual art, such as form, colour, symmetry, complexity, luminance and contrast (Bar & Neta, 2006;Bona et al, 2015;Graham et al, 2016;Hayn-Leichsenring et al, 2020;Iigaya et al, 2021;Jacobsen & Höfel, 2003;Jacobsen et al, 2006;Nadal et al, 2010;Palmer & Schloss, 2010;Van Geert & Wagemans, 2019;Vartanian et al, 2013). Although many different visual features of art have been studied from a neuroscientific perspective, it is maybe surprising that implied motion has only received limited attention (Di Dio et al, 2016;Kim & Blake, 2007;Thakral et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroaesthetics research has focussed on deconstructing features of visual art, such as form, colour, symmetry, complexity, luminance and contrast (Bar & Neta, 2006;Bona et al, 2015;Graham et al, 2016;Hayn-Leichsenring et al, 2020;Iigaya et al, 2021;Jacobsen & Höfel, 2003;Jacobsen et al, 2006;Nadal et al, 2010;Palmer & Schloss, 2010;Van Geert & Wagemans, 2019;Vartanian et al, 2013). Although many different visual features of art have been studied from a neuroscientific perspective, it is maybe surprising that implied motion has only received limited attention (Di Dio et al, 2016;Kim & Blake, 2007;Thakral et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of aesthetic judgements, there is a need, therefore, to move into multivariate space (Kriegeskorte, 2009;Norman et al, 2006). Some neuroaesthetics work has started to approach questions using multivariate classifiers (Iigaya et al, 2021). More generally, human neuroscience research on functional integration or how multiple brain systems interact with one another for a given process (Bullmore & Sporns, 2009;Park & Friston, 2013) is particularly relevant here because we want to estimate how and when signals from distinct circuits are integrated in the process of constructing an aesthetic judgement.…”
mentioning
confidence: 99%
“…Thus, self-relevance is a key determinant of aesthetic appeal, independent of artistic skill and image features.Recently it has been shown that a linear combination of low-and high-level image features predicts, on average, around 20% of variance in observer ratings [2]. A comparable performance (16.4%) was obtained by a deep neural network trained to predict aesthetic ratings [2]. These findings suggest that a large fraction of variance in aesthetic ratings across individuals remains unexplained.…”
mentioning
confidence: 81%
“…Self-relevant, synthetic artworks were rated as more aesthetically appealing than matched control images, at a level similar to real artworks. Thus, self-relevance is a key determinant of aesthetic appeal, independent of artistic skill and image features.Recently it has been shown that a linear combination of low-and high-level image features predicts, on average, around 20% of variance in observer ratings [2]. A comparable performance (16.4%) was obtained by a deep neural network trained to predict aesthetic ratings [2].…”
mentioning
confidence: 88%
See 1 more Smart Citation